THE ORGANIZATION OF THE STATE SYSTEM OF MAKING PREDICTIONS IN THE ELECTRICITY INDUSTRY UNITED STATES - Y. Aleksandrov (Publishing House of the State University of Management, 2017)
In the conditions of reforming of power industry and development of the market relations an important role is played by the government institutions which are carrying out regulation of activity of the energy companies. In article experiment of the USA on the organization of effective system of providing authorities with information necessary for formation of qualitative forecasts of development of branch is considered.